Confirmation of Soil-Transmitted-Helminths Infection Prevalence by Kato-Katz Kit Diagnostic in Elementary School Children in West Martapura River Banks, South Kalimantan Indonesia - Rifqoh, Rifqoh; Cahyono, Jujuk Anton; Kustiningsih, Yayuk (Tropical Health and Medical Research, 2023)
Soil-Transmitted Helminths (STH) infections are the most widespread neglected tropical diseases, primarily affecting morbidity in School Age Children (SAC). STH infection in SAC remains a public health problem in Martapura River Banks. Early and accurate STH detection is essential to determine an effective treatment for reducing morbidity. The Health Department recommends detecting STH infection by Kato Katz (KK) but in public health centers only by the direct method. This research objective is to confirm STH infection prevalence by Kato-Katz (KK) in elementary school children in West Martapura River Banks, South Kalimantan, Indonesia, against the direct method. The modified KK templates were developed from acrylic material. A total number of 253 children 7-12 years old in four West Martapura elementary schools were examined for STHs eggs using both microscopies modified KK against direct method by two trained laboratory technicians. STHs infection prevalence was 50 (19.76%), interpreted as low prevalence by direct and 78 (30.83%), moderate by KK. The concordance between both methods was significantly based on Cohen’s kappa (?=0.682). Even though the concordance of both methods was strong, the prevalence of STHs by modified KK was 30.08% higher than by Direct, which was only 20.33% positive. This study recommended using the KK for STHs diagnostic for prevalence measurement in low STHs infection.